Transabdominal Insonation of Fetal Basilar Artery: A Feasibility Study. Issue 2 (21st December 2015) - Qureshi, Adnan I.; Miran, Muhammad Shah; Degenhardt, Jan; Axt‐Fliedner, Roland; Kohl, Thomas
ABSTRACT: BACKGROUND: Fetal anterior, middle, and posterior cerebral arteries have been studied using transabdominal Doppler ultrasound. We performed a feasibility study to determine whether basilar artery can be identified and blood flow velocities measured using transabdominal fetal Doppler ultrasound. METHODS: The basilar artery was identified in sagittal plane behind the clivus bone using directional color Doppler with 6‐2 and 7‐4 MHz curved array probes. The clivus was identified by hyperechoic linear signal anterior to junction of vertebral processes and occipital bone and superior to first vertebral body. The flow direction was away from the probe in the basilar artery consistent with caudo cephalic orientation. The Doppler ultrasound probe was placed at insonation angles of less than 30° at the visualized segment of the basilar artery. Peak systolic and end diastolic velocities were measured. RESULTS: We attempted insonation of the basilar artery in 20 fetuses. The basilar artery was adequately insonated in 18 fetuses with a mean gestational age of 27 weeks (range 19 to 38 weeks). The mean value (±SD) of peak systolic velocity of the basilar artery was 22.1 ± 8.5 cm/second (range 10.4‐36.7 cm/second). The mean value (±SD) of end diastolic velocity was 6.8 ± 2.8 cm/second (range 3.5‐13.5 cm/second). There was an increase in peak systolic velocity values according to gestational age of fetus. CONCLUSIONS: We demonstrate the feasibility of fetal basilar artery insonation using directional color Doppler ultrasound via transabdominal approach.